The influence of the merger process between two tertiary hospitals in Romania on job satisfaction among staff - Ilea, Codrin Dan Nicolae; Daina, Lucia Georgeta; Manole, Felicia; Daina, Mădalina Diana; Tirt, Dorel Petru; Popa, Anca (Frontiers in Psychology, 2024)
The purpose of this study is to evaluate the influence of the merger process of two tertiary hospitals located in the northwest of Romania on the professional satisfaction among medical and non-medical staff and to develop a standardized satisfaction questionnaire for romanian hospitals.Methods: 1750 questionnaires distributed within County Clinical Emergency Hospital Bihor (CCEHBh) ten months and one year and four months after the merger process were analyzed.The percentage of staff who declare themselves satisfied with their work one year and four months after the merger is 80.14%. It has a downward trenddecreasing tendency compared to the result measured ten months after the merger (86.14%)(χ 2 test, p < 0.01). The aspects that were rated withappreciated in the lowest percentage as satisfactory were the possibility of promotion (41.89%) and job security (53.38%). A statistically significant decrease was also recorded in the assessment of career prospects (from 81.49% to 74.73%, χ 2 test, p < 0.0001).Even if there was a decrease in job satisfaction between the two evaluated periods, we can state that the general level at the last measurement is a good one (4.07 out of a maximum of 5). There was no significant difference in job satisfaction one year and four months after the merger for staff in the merged unit (4.06) compared to staff in the absorbing unit (4.09) 1 Codrin Dan Nicolae Ilea et al.No significant difference was found in job satisfaction one year and four months after the merger for staff from the assimilated unit (4.06) versus staff from the assimilating unit (4.09).The questionnaire applied in 2023 is one that has proven validity and reliability, being a good starting point for creating a standardized questionnaire that could be implemented in the vast majority of hospitals in Romania. The application of the questionnaire at an intervalover a period of 3-6 months would highlight the result of the implemented measures and the trend of employee satisfaction trend within the CCEHBh.